Assessment of a multi-assay biological diagnostic test for mood disorders in a Japanese population. (26th January 2016) - Yamamori, Hidenaga; Ishima, Tamaki; Yasuda, Yuka; Fujimoto, Michiko; Kudo, Noriko; Ohi, Kazutaka; Hashimoto, Kenji; Takeda, Masatoshi; Hashimoto, Ryota
Highlights: Plasma levels of three biomarkers for mood disorders were measured. The plasma sTNFR2 levels were higher in the BD and schizophrenia patients. The plasma EGF levels were higher in the BD patients. The plasma myeloperoxidase levels were higher in the BD patients. Abstract: The current diagnostic tests for mood disorders, including major depressive disorder (MDD) and bipolar disorder (BD), have limitations. Inflammatory markers, growth factors, and oxidative stress markers are involved in the pathophysiology of mood disorders. A multi-assay biological diagnostic test combining these biomarkers might improve diagnostic efficiency. The plasma levels of soluble tumor necrosis factor receptor 2 (sTNFR2), epidermal growth factor (EGF), and myeloperoxidase were measured in 40 MDD patients, 40 BD patients and 40 controls in a Japanese population. We also investigated the plasma levels of these markers in 40 patients with schizophrenia to determine the utility of these markers in differential diagnosis. The plasma levels of sTNFR2 were significantly higher in BD and schizophrenia patients than in controls. The plasma levels of EGF and myeloperoxidase were significantly higher in patients with BD than in controls. The correct classification rate obtained from discriminant analysis with sTNFR2 and EGF between controls and mood disorders was 69.2%, with a sensitivity and specificity of 62.5% and 82.5%, respectively. The correct classification rate obtained from discriminant analysis with sTNFR2 and EGF between controls and BD was 85.0%, with a sensitivity and specificity of 77.6% and 92.5%, respectively. Our results suggest that sTNFR2 and EGF could be biological markers of BD. Further studies are needed to determine the utility of these markers in diagnostic tests for mood disorders.